SAT0678 Significantly increased seropositivity, rheumatoid factor titres and rheumatoid nodules in cornish kaolin workers. (15th June 2017) - Murphy, D; Fleeming, E; Bellis, K; Hutchinson, D
Abstract : Background: Kaolin has been mined in Cornwall, UK for over 250 years, with half of the world's production originating from the area at the turn of the 20th century. Mineral kaolinite does not react as free silica, and is used in heavy metal contamination containment due to its adsorption capabilities. 1 Objectives: To investigate the prevalence of occupational kaolin dust exposure in male rheumatoid arthritis (RA) patients in Cornwall, UK. Methods: All males diagnosed with RA under follow up at the Royal Cornwall Hospital, UK, during the study period April 2015-January 2017, were invited to complete an occupational questionnaire, detailing current occupation, last occupation (if retired) and other occupations for >1 year. Results: 39/720 (5%) cases were excluded on non-return of initial questionnaires. 41/720 (6%) cases died during the study period (22 months). 54/640 (8%) remaining cases had occupational kaolin exposure, approximately 12 times higher than expected based on current census employment rates. 30/54 had long term kaolin dust exposure, living in the post code region PL22-PL26 (total male population 33693). These were matched for age ±2 years, sex and index of multiple deprivation (IMD) ±1 decile, to RA patients with no occupational dust or fume exposure. 40/110 potential controls were successfully matched. Significantly more RA kaolin workers were seropositive for RF and ACPA than non-dust exposed RA controls (Table 1 ). Of RF seropositive patients, median RF titres were significantly higher in kaolin workers than unexposed controls (p<0.01). No significant differences were seen in ACPA titre. Smoking prevalence rates were not significantly different between kaolin workers and controls. Amongst ever smokers, median pack years smoked showed no difference between cases and controls. Kaolin exposed never smokers demonstrated significantly higher RF titres than unexposed never smokers (kaolin median RF 109 (IQR 32–193.5), control median RF 24 (IQR 7–61), p<0.04), as did kaolin exposed smokers (kaolin median RF 146.7 (IQR 56–231.5), control median RF 61 (IQR 18.5–170), p<0.03, figure 1 ). Interestingly, 7/30 (23%) kaolin workers demonstrated nodular disease, compared to 3/40 (7.5%) matched controls, p=0.06, significantly higher than the background nodular rate 79/720 (11%) of male RA patients throughout Cornwall, p<0.04. Conclusions: Kaolin dust exposure in RA confers higher RF and ACPA seropositivity rates and higher RF titres. Smoking and kaolin dust exposure have an additive effect on RF titres. Higher rates of nodular disease are seen in RA patients exposed to kaolin dust, independent of smoking. We hypothesise that this interaction is due to adsorption of heavy metals from tobacco smoke or other environmental sources by kaolin particles, stimulating autoantibody production. References: Matlok M, Petrus R, Warchol JK. Equilibrium study of heavy metals adsorption on Kaolin. Ind Eng Chem Res 2015; 54(27):6975–84. Acknowledgements: Cornwall Arthritis Trust. Disclosure of Interest: None declared